Cold Dust Emission from X-ray AGN in the SCUBA-2 Cosmology Legacy Survey: Dependence on Luminosity, Obscuration and AGN Activity - Banerji, M; McMahon, R; Willott, C; Geach, J; Harrison, C; Alaghband-Zadeh, S; Alexander, D; Bourne, N; Coppin, K; Dunlop, J; Farrah, D; Jarvis, M; et al. (Oxford University Press, 2015)
We study the 850um emission in X-ray selected AGN in the 2 sq-deg COSMOS field using new data from the SCUBA-2 Cosmology Legacy Survey. We find 19 850um bright X-ray AGN in a high-sensitivity region covering 0.89 sq-deg with flux densities of S850=4-10 mJy. The 19 AGN span the full range in redshift and hard X-ray luminosity covered by the sample - 0.7<z<3.5 43.2<log10(lx)="" 699="" 850um="" <45.="" a="" and="" detection="" flux-limited="" hard="" highly="" of="" population="" report="" significant="" stacked="" we="" x-ray="" z="">1 X-ray AGN - S850=0.71+/-0.08mJy. We explore trends in the stacked 850um flux densities with redshift, finding no evolution in the average cold dust emission over the redshift range probed. For Type 1 AGN, there is no significant correlation between the stacked 850um flux and hard X-ray luminosity. However, in Type 2 AGN the stacked submm flux is a factor of 2 higher at high luminosities. When averaging over all X-ray luminosities, no significant differences are found in the stacked submm fluxes of Type 1 and Type 2 AGN as well as AGN separated on the basis of X-ray hardness ratios and optical-to-infrared colours. However, at log10(LX) >44.4, dependences in average submm flux on the optical-to-infrared colours become more pronounced. We argue that these high luminosity AGN represent a transition from a secular to a merger-driven evolutionary phase where the star formation rates and accretion luminosities are more tightly coupled. Stacked AGN 850um fluxes are compared to the stacked fluxes of a mass-matched sample of K-band selected non-AGN galaxies. We find that at 10.5</z<3.5>